Wild-type TTR amyloidosis among patients with unexplained heart failure and systolic LV dysfunction. - Sorel Goland; Igor Volodarsky; Yacov Fabricant; Shay Livschitz; Sagi Tshori; Valeri Cuciuc; Liaz Zilberman; Irena Fugenfirov; Valeri Meledin; Sara Shimoni; Sagie Josfberg; Jacob George (PLoS ONE)
Aim Transthyretin cardiac amyloidosis (ATTR-CA) is an increasingly recognized cause of heart failure (HF) with preserved left ventricular ejection fraction (LVEF), typically presenting as restrictive cardiomyopathy. The potential co-existence of ATTR-CA with systolic heart failure has not been studied. The aim of this study is to describe the prevalence of ATTR-CA and its clinical characteristics in HF patients with reduced LVEF. Methods Patients with an unexplained cause of LV systolic dysfunction were screened for ATTR-CA by a 99mTc-PYP planar scintigraphy. Patients in whom presence of ≥ 2 uptake was confirmed by SPECT imaging were included. Their clinical, laboratory and echocardiographic data were collected. Results Out of 75 patients (mean age 65±12 years, LVEF 35.8±7.9%) included in this study, 7 (9.3%) patients (mean age 75±6 years, LVEF 32.0±8.3%) had ATTR-CA. Patients with ATTR-CA were more symptomatic at diagnosis (NYHA FC 3-4 (86% vs 35% (p = 0.03)) and had a more severe clinical course evident by recurrent hospitalizations for HF, and a need for intravenous diuretic treatment (p = 0.04 and p<0.01, respectively) at follow-up, compared with patients with no ATTR-CA. Patients with ATTR-CA had similar LVEF but a clear trend for larger LV mass index (157.1±60.6 g/m2 vs. 121.0±39.5 g/m2, p = 0.07) and a larger proportions of ATTR-CA patients had IVS thickness >13 mm (57.1% vs 13.1%, p = 0.02) as compared to HF patients with no ATTR-CA. Conclusion In our study, a meaningful percentage of patients with unexplained LV dysfunction had a co-existing ATTR-CA indicating that the clinical heterogeneity of ATTR-CA is much broader than previously thought.